Influence of Nutrient Addition on the Bioethanol Yield from Oil Palm Trunk Sap Fermented by Saccharomyces Cerevisiae - Nor Shahirah, Mohd Nasir; Jolius, Gimbun; Sook, Fun Pang; Rossyuhaida, Mohd Zakria; Cheng, C. K.; Chua, Gek Kee; Mohd Fazli, Farida Asras (Elsevier, 2015)
This paper presents the influence of nutrient addition namely MgSO4, C3H7NO2, (NH4)2SO4 and Na2HPO4 to the bioethanol yield from oil palm trunk saps (OPTS) with fermentation carried out by Saccharomyces cerevisiae. The sugar and ethanol contents in the sample were determined using a high-performance liquid chromatography. Nutrient addition has improved the bioethanol yield markedly, with the average yield ranged from 58.50% to 77.12% compared to about 51.08% without nutrient addition. The highest bioethanol yield (81.89%) was achieved by adding MgSO4. The rank of nutrient influence on improving the bioethanol yield was MgSO4 > C3H7NO2 > (NH4)2SO4 > Na2HPO4